Short-Term Outcome of Mechanical Ventilation in Neonates - Gurubacharya, SM; Aryal, DR; Misra, M; Gurung, R (Journal of Nepal Paediatric Society, 2011)
Mechanical ventilation of newborn has been practiced for several years with several advances made in the way. As compared to the Western world and our neighbouring countries, neonatal ventilation in our country is still in its infancy. Objectives: To analyze the common indications and outcome of neonates requiring mechanical ventilation. Methods: This was a prospective observational study conducted on neonates requiring mechanical ventilation within first 24 hours of birth over a period of nine months. Results: Birth asphyxia was the commonest indication for ventilation (59.67%) followed by asphyxia with meconium aspiration syndrome (MAS) (17.74%), hyaline membrane disease (HMD) (8.06%), MAS (6.45%) and intrauterine pneumonia (6.45%). Out of 62 babies, 22 (35.48%) survived. Babies with asphyxia had highest survival rate (51.35%). Neonates with HMD did not survive. Term babies and babies weighing ≥2500g had higher survival rate of 40.47% and 41.46% respectively, while babies less than 32 weeks had survival rate of 16.66% only. Conclusions: Mechanical ventilation reduces the neonatal mortality; hence, facilities for neonatal ventilation should be included in the regional and central hospitals providing level II neonatal care. Key words: neonatal ventilation; hyaline membrane disease; low birth weight DOI: 10.3126/jnps.v31i1.3463 J Nep Paedtr Soc 2010;31(1):35-38